Molecular epidemiology and genetic diversity of Plasmodium knowlesi infecting long-tailed macaques (Macaca fascicularis Raffles) on the west coast of Peninsular Malaysia - Lee, Col Lin (2015)
This study was undertaken to ascertain the molecular epidemiology of Plasmodium knowlesi infecting wild Long-tailed macaques (Macaca fascicularis) on the west coast of Peninsular Malaysia, and to determine its spatial distribution and risk factors for infection. Genetic analysis based on the Circumsporozoite Protein (CSP) gene of P. knowlesi was done to infer the genetic assemblage of the parasite. A total of 781 blood samples were collected from wild M. fascicularis captured from 77 locations representing four different habitats; urban, sub-urban, plantation/orchards and secondary forest. Five states on the west coast of the country were sampled, namely, Penang, Perak, Selangor, Negeri Sembilan and Melaka, and the area was arbitrary divided into three zones. Ten human infected blood samples from Kuala Kubu Baru, Selangor were included in the study. Screening for P. knowlesi infection was conducted using nested PCR targeting the 18S SSU rRNA and phylogenetic characterization was done using the CSP gene. Prevalence of infection was 13.4% (15.1% male and 11.1% female) with Zone 1 exhibiting the highest prevalence (29.8%), followed by Zone 3 (15.6%) and Zone 2 (5.3%). Macaques inhabiting the plantation/orchards were the most infected (18.2%), followed by sub-urban (16.5%), secondary forest (15.7%), and urban (9.8%) areas. The adult macaques showed the highest prevalence of P. knowlesi infection (16.6%), followed by the juveniles (13.1%) and sub-adults (9.7%). Spatial distribution analysis revealed two hotspots of infection in the country; on the northwest (Penang and north Perak) and southwest (Negeri Sembilan). Risk factor analysis showed that all putative factors except gender, posed a risk for infection with this parasite among the macaques. Stepwise binary logistic regression analysis revealed that macaques from Zone 1, sub-urban and plantation/orchards, and adults, have higher risk of infections compared to conspecifics in the other categories. Genotypic analyses of 192 P. knowlesi CSP gene sequences (178 from macaques and 14 from humans) produced 25 different haplotypes with 14 polymorphic sites. The overall nucleotide diversity (pi = 0.0196) and haplotype diversity (Hd = 0.836) was high, but genetic differentiation between the zones and habitats was low (FST<0.05). The three most commonly encountered haplotypes PkMH18 (f = 62), PkMH13 (f = 26) and PkMH04 (f = 18), were widely distributed across the sampling locations, with the former predominating in the northwest region of the country. All eight haplotypes from humans were found to be identical with that obtained from the macaques. Phylogenetic analysis clustered macaque and human isolates from within the Southeast Asia region. This study represents the first attempt to elucidate the molecular epidemiology, spatial distribution and genetic diversity of P. knowlesi infection among M. fascicularis in Peninsular Malaysia. Increasing destruction of forest habitats for human activities in Southeast Asia has narrowed the malaria transmission interface between macaques and humans. Comprehensive epidemiological investigations should be carried out in order to shed more light on the transmission dynamics of this deadly zoonotic disease in the region.